Rapid assessment with physical examination in dyspnoeic cats: the RAPID CAT study. (9th November 2017) - Dickson, D.; Little, C. J. L.; Harris, J.; Rishniw, M.
Abstract : Objectives: To determine the underlying disease prevalence in acute feline dyspnoea and to examine whether historical and clinical examination findings can differentiate between acute cardiac and non‐cardiac dyspnoea in cats in primary practice. Materials and Methods: We prospectively enrolled cats presenting with dyspnoea for the first time to primary practice between June 1, 2011 and October 31, 2016. We collected signalment, historical and clinical data at presentation using a standard form. Cases were investigated by primary clinicians, and the final diagnosis was confirmed by the authors. Records lacking critical data were excluded. Relationships between historical or clinical variables and dyspnoea aetiology were examined. Diagnostic test performance analyses were used to find optimal cut‐off values for select historical or clinical variables that could differentiate cardiac and non‐cardiac dyspnoea. Results: Participants included 108 cats. A definitive diagnosis was reached in 92 cases; 60 were cardiac (65%), 15 respiratory (16%), 10 neoplastic (11%) and 7 traumatic (8%). Of cats with cardiac dyspnoea, 25% had a history of cough. A gallop sound, rectal temperature less than 37·5°C, heart rate of greater than 200 bpm and respiratory rate greater than 80 per minute were all useful to predict cardiac‐associated dyspnoea. A triage algorithm using these findings in combination was designed to optimise the rapid diagnosis of probable cardiac dyspnoea. Clinical Significance: Dyspnoeic cats presenting in practice with hypothermia, tachycardia, gallop sounds or profound tachypnoea are likely to have a cardiac cause underlying their dyspnoea. Although diagnosis requires confirmation, clinicians may be able to stratify risk and prioritise further investigation based on these findings.